Battery active material as well as preparation and application thereof
By developing a sodium ion battery positive electrode active material with chemical formula Na0.67Zn(0.28-x)FexMn0.72O2, the problems of low energy density and high cost of sodium ion battery are solved, and the effects of high energy density and low cost are achieved.
Patent Information
- Application Number
- CN202411361099.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Sodium ion batteries have lower energy density and higher costs, especially due to their dependence on expensive metals such as nickel, which limits their practical application.
A low-cost, high-specific energy positive electrode active material based on the oxidation and anions involved in the redox reaction was developed. The chemical formula is Na0.67Zn(0.28-x)FexMn0.72O2, 0
It achieves high energy density (up to 549.94Wh/kg), good cycle stability and low cost, and is suitable as an ideal positive electrode material for sodium ion batteries.
Smart Images

Figure CN119419259A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a battery active material, and its preparation and application. Background Art
[0002] In recent years, sodium-ion batteries have become good candidates for large-scale energy storage devices due to their potential high resource abundance and low cost, and are expected to promote the efficient use of clean energy as energy storage devices.
[0003] However, since the molar mass of sodium ions is much greater than that of lithium ions, the energy density of sodium ion batteries is often lower than that of lithium ion batteries under normal conditions.
[0004] In addition, current sodium-ion battery materials still rely on some expensive metals (such as nickel), resulting in relatively high costs. Therefore, how to explore effective methods to reduce costs and increase efficiency from a scientific perspective is the key bottleneck for the current sodium-ion battery to move towards practical application. Summary of the invention
[0005] In view of this, the present application discloses a low-cost, high-energy-density sodium ion battery positive electrode active material based on the co-participation of cations and anions in the redox reaction. 0.67 Zn (0.28-x) FexMn 0.72 O2, and 0 <x≤0.2。
[0006] The active material has high energy density (up to 549.94Wh / kg), good cycle stability, and the preparation method is simple and easy to operate with high yield. It is composed of cheap metals and has a low price.
[0007] This application is implemented through the following: An electrode active material for sodium ion batteries, with the chemical formula Na 0.67 Zn 0.28-x Fe x Mn 0.72 O2, where 0 <x≤0.2。
[0008] A method for manufacturing an electrode active material for a sodium ion battery, characterized in that the method comprises: providing a precursor powder containing at least a sodium source compound, a zinc source compound, an iron source compound and a manganese source compound in a preset ratio; and calcining the precursor powder, wherein the chemical formula of the active ingredient is Na 0.67 Zn (0.28-x) Fe x Mn 0.72 O2,0 <x≤0.2。
[0009] The present application also provides a sol-gel preparation method of the above material, comprising the following steps: After dissolving a sodium source compound, a zinc source compound, an iron source compound and a manganese source compound in water with a chelating agent according to a molar ratio, heating to volatilize the solvent, a gel precursor is obtained; The gel precursor is dried and then ground to obtain a precursor powder; The precursor powder was calcined twice in sequence.
[0010] The present application also provides a solid phase preparation method of the above material, comprising the following steps: The sodium source compound, the nickel source compound, the copper source compound, the zinc source compound and the manganese source compound are mixed by solid phase ball milling according to a molar ratio to obtain a precursor powder; The precursor powder is calcined once or twice.
[0011] The present application also provides a method for spray drying the above material, comprising the following steps: Dissolving a sodium source compound, a zinc source compound, an iron source compound and a manganese source compound in water according to a molar ratio, and mixing them by ball milling to obtain a precursor solution; The precursor solution is injected into a spray dryer for spray drying, and then ground after drying to obtain a precursor powder; The precursor powder was calcined twice in sequence.
[0012] The present application also discloses an application of the aforementioned electrode active material in manufacturing a positive electrode material for a sodium ion battery.
[0013] The present application also discloses a sodium ion battery positive electrode material, which comprises the above-mentioned electrode active material.
[0014] The present application also provides a sodium ion battery positive electrode sheet, which is prepared from a positive electrode material, a conductive additive, a binder and a solvent, and the positive electrode material is selected from the above positive electrode materials.
[0015] The present application also discloses a positive electrode sheet, which includes: a positive electrode current collector, and a positive electrode active layer arranged on at least one side surface of the positive electrode current collector, and the positive electrode active layer is made of electrode active material or positive electrode material.
[0016] The present application also discloses a battery, including: an electrode active material, a positive electrode material, or a positive electrode sheet.
[0017] The present application also discloses an electrical device, comprising the above-mentioned battery.
[0018] The present application also provides an application of the above-mentioned sodium ion battery in large-scale energy storage devices for solar power generation, wind power generation, smart grid peak regulation, distributed power stations or communication bases.
[0019] Beneficial effects: The present application provides a low-cost, high-specific-energy active material that can be used as a positive electrode material for sodium ion batteries, and its chemical formula is Na 0.67 Zn (0.28-x) FexMn 0.72 O2(0 <x≤0.2)。
[0020] The positive electrode material provided in the present application has the excellent properties of high specific capacity, high stability, high energy density, moderate output voltage and low cost, and can be used as an ideal positive electrode material for sodium ion batteries.
[0021] In addition, the positive electrode material provided in the present application also has the advantages of simple synthesis process, easy control, and easy mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] For a clearer explanation, the following briefly introduces the drawings required for the description.
[0023] Figure 1 Figure A is the XRD spectrum of the target product obtained in Example 1, and Figure B is the SEM image of the target product obtained in Example 1.
[0024] Figure 2 Figure A shows the target product obtained in Example 1 at 10 mA g -1 The charge-discharge curves under current density, Figure B is the cyclic voltammetry curve of the target product obtained in Example 1 at a scan rate of 0.1 mV / s, and Figure C is the cyclic voltammetry curve of the target product obtained in Example 1 at a scan rate of 50 mA g -1 Figure D shows the cycling stability of the energy density of the target product obtained in Example 1 at 10 mA g -1 Cycling stability at different current densities.
[0025] Figure 3 The XRD spectrum of the target product obtained in Comparative Example 1 is shown in FIG.
[0026] Figure 4 Figure A shows the target product obtained in Comparative Example 1 at 10 mA g -1 The charge-discharge curves under current density, Figure B shows the target product obtained in Comparative Example 1 at 10 mA g -1 Cycling stability at different current densities.
[0027] Figure 5 The XRD spectrum of the target product obtained in Example 2 is shown in FIG.
[0028] Figure 6 Figure A shows the target product obtained in Example 2 at 10 mA g -1The charge-discharge curves under current density, Figure B shows the target product obtained in Example 2 at 10 mA g -1 Cycling stability at different current densities.
[0029] Figure 7 The XRD spectrum of the target product obtained in Example 3 is shown in FIG.
[0030] Figure 8 Figure A shows the target product obtained in Example 3 at 10 mA g -1 The charge-discharge curves under current density, Figure B shows the target product obtained in Example 3 at 10 mA g -1 Cycling stability at different current densities.
[0031] Fig. 9 The XRD spectrum of the target product obtained in Example 4 is shown in FIG.
[0032] Fig.10 Figure A shows the target product obtained in Example 4 at 10 mA g -1 The charge-discharge curves under current density, Figure B shows the target product obtained in Example 4 at 10 mA g -1 Cycling stability at different current densities.
[0033] Fig.11 The XRD spectrum of the target product obtained in Example 5 is shown in FIG.
[0034] Fig.12 Figure A shows the target product obtained in Example 5 at 10 mAg -1 The charge-discharge curves under current density, Figure B shows the target product obtained in Example 5 at 10 mA g -1 Cycling stability at different current densities.
[0035] Fig.13 The XRD spectrum of the target product obtained in Example 6 is shown in FIG.
[0036] Fig.14 Figure A shows the target product obtained in Example 6 at 10 mA g -1 The charge-discharge curves under current density, Figure B shows the target product obtained in Example 6 at 10 mA g -1 Cycling stability at different current densities.
[0037] Fig.15 The XRD spectrum of the target product obtained in Example 7 is shown in FIG.
[0038] Fig.16 Figure A shows the target product obtained in Example 7 at 10 mA g -1 The charge-discharge curves under current density, Figure B shows the target product obtained in Example 7 at 10 mA g -1Cycling stability at a current density.
[0039] Fig.17 XRD pattern of the target product obtained in Example 8.
[0040] Fig.18 In Figure A, the charge-discharge curve of the target product obtained in Example 8 at a current density of 10 mA g -1 and in Figure B, the cycling stability of the target product obtained in Example 8 at a current density of 10 mA g -1 current density.
[0041] Fig.19 XRD pattern of the target product obtained in Example 9.
[0042] Fig. 20 In Figure A, the charge-discharge curve of the target product obtained in Example 9 at a current density of 10 mA g -1 and in Figure B, the cycling stability of the target product obtained in Example 9 at a current density of 10 mA g -1 current density. Detailed implementation manners
[0043] The chemical formula of the low-cost and high specific energy sodium ion battery active material provided by this application is Na 0.67 Zn 0.28- x Fe x Mn 0.72 O2.
[0044] Where 0 < x ≤ 0.2, preferably 0 < x < 0.2. Or 0 < x < 0.05, or 0.07 < x < 0.09, or 0.1 < x < 0.14, or 0.15 < x < 0.2; or 0 < x < 0.16.
[0045] Experimental verification shows that as the content of Fe in the sodium ion battery active material increases, the energy density of this system material is greater and the initial discharge specific capacity is greater. The cycling stability is the best when x = 0.15.
[0046] Microscopically, this active material is a layered oxide particle material, and the particle size is 1 - 5 μm - it can also be 1 - 3 μm, 2 - 4 μm, 2 - 5 μm, 1 - 4 μm, 3 - 5 μm, etc.
[0047] Different from the traditional cathode materials where cations participate in redox reactions, the cathode formed using the above active material can achieve a high energy density of 549.94 Wh / kg under the synergistic action of cations and anions (see Table 1 and Table 2).
[0048] Table 1 records the data of the active materials in the examples of this application and the components of several active materials used as comparative examples. Table 2 records the data of the comparison of the specific capacity and energy density of different components.
[0049] Table 1
[0050] Table 2
[0051] In order to provide a more complete disclosure and facilitate those skilled in the art to implement the solutions of the present application, a variety of preparation methods of the above-mentioned exemplified active materials of the present application are also provided below.
[0052] Method 1 The sol-gel method comprises the following steps: A) dissolving a sodium source compound, a zinc source compound, an iron source compound and a manganese source compound in water with a chelating agent according to a molar ratio; then, heating to volatilize the solvent to obtain a gel precursor; B) drying the gel precursor and then grinding it to obtain a precursor powder; C) The precursor powder is calcined twice in sequence to obtain the active material.
[0053] This example uses the sol-gel method to synthesize the positive electrode active material for sodium ion batteries.
[0054] (1) First, prepare the gel precursor.
[0055] Specifically, a sodium source compound, a zinc source compound, an iron source compound and a manganese source compound are dissolved in water together with a chelating agent according to a desired stoichiometric ratio to obtain a mixed solution / sol.
[0056] The ratio of the total molar amount of metal ions in the sodium source compound, the zinc source compound, the iron source compound and the manganese source compound to the molar amount of the chelating agent is 1:(1-3).
[0057] Each raw material can be selected according to the components exemplified below.
[0058] The sodium source compound is a water-soluble sodium source compound, for example, it can be selected from one or more of sodium acetate, sodium nitrate, sodium oxalate and sodium citrate. Preferably, the water-soluble sodium source compound is sodium acetate.
[0059] The zinc source compound is a water-soluble zinc source compound, for example, it can be selected from one or more of zinc acetate, zinc nitrate, zinc oxalate, zinc sulfate and zinc chloride. Preferably, the water-soluble zinc source compound is zinc acetate.
[0060] The iron source compound is a water-soluble copper source compound, for example, it can be selected from one or more of ferric acetate, ferric nitrate, ferric oxalate, ferric sulfate and ferric chloride. Preferably, the water-soluble copper source compound is ferric acetate.
[0061] The manganese source compound is a water-soluble manganese source compound, for example, it can be selected from one or more of manganese acetate, manganese nitrate, manganese oxalate, manganese sulfate and manganese chloride. Preferably, the water-soluble manganese source compound is manganese acetate.
[0062] The chelating agent may be selected, for example, from citric acid, oxalic acid, tartaric acid or ethylenediaminetetraacetic acid.
[0063] (2) After obtaining the mixed solution, the solvent is evaporated by heating to obtain a gel precursor.
[0064] The heating method in this step can be an oil bath, and stirring can also be performed during the oil bath.
[0065] (3) After obtaining the gel precursor, the gel precursor is dried and then ground to obtain a precursor powder.
[0066] The drying temperature and time can be any suitable temperature and time, and the present application has no particular choice for this. Generally, the temperature and time are selected based on, for example, being able to make the water content of the precursor gel lower than 1wt%.
[0067] (4) Then, the precursor powder is calcined twice in sequence to obtain the positive electrode material for a sodium ion battery.
[0068] In this step, both calcinations are performed under an air atmosphere, and based on the convenience of description, it can be described as the first calcination and the second calcination being performed sequentially.
[0069] The first calcination has a heating rate of 2°C / min, the temperature is raised to 350-600°C, preferably 450°C, and the temperature is kept until the organic matter is fully decomposed; the second calcination has a heating rate of 2°C / min, the temperature is raised to 750-1000°C, preferably 750-800°C, and the temperature is kept for 10-24 hours.
[0070] Method 2 The solid phase method comprises the following steps: A) mixing a sodium source compound, a zinc source compound, an iron source compound and a manganese source compound according to a desired molar ratio by solid phase ball milling to obtain a precursor powder; B) The precursor powder is calcined once or twice to obtain the active material.
[0071] The sodium source compound is selected from one or more of sodium oxide, sodium carbonate, sodium acetate, sodium nitrate, sodium oxalate and sodium citrate, preferably sodium oxide or sodium carbonate; The zinc source compound may be selected from one or more of zinc oxide, zinc acetate, zinc nitrate, and zinc oxalate, preferably zinc oxide or zinc acetate; The iron source compound may be selected from one or more of iron oxide, iron acetate, iron nitrate, and iron oxalate, preferably iron oxide or iron acetate; The manganese source compound can be selected from one or more of manganese oxide, manganese acetate, manganese nitrate, and manganese oxalate, preferably manganese oxide or manganese acetate.
[0072] The precursor powder is uniformly obtained by ball milling, and then the precursor powder is calcined once or twice in sequence to obtain the positive electrode material of the sodium ion battery.
[0073] In the method of this example, the number of times the precursor is calcined can be determined according to the specific composition of the raw materials.
[0074] For example, when the raw materials for preparing the precursor powder are all oxides (i.e., the aforementioned sodium oxide, zinc oxide, iron oxide, and manganese oxide), the calcination is performed once. An exemplary heating system can be exemplified as a heating rate of 2°C / min, heating to 750-1000°C (preferably 750-800°C), and keeping the temperature for 10-24h until a P2 phase structure without impurities is formed.
[0075] When the raw materials for the preparation of the precursor powder are all salts (such as acetate, nitrate and oxalate), the calcination is carried out twice, and is described as the first calcination and the second calcination performed in sequence. The specific optional heating system is: the heating rate of the first calcination is 2℃ / min, the temperature is raised to 450℃, and the temperature is kept until the salts are decomposed into oxides; the heating rate of the second calcination is 2℃ / min, the temperature is raised to 750~1000℃ (preferably 750~800℃), and the temperature is kept for 10~24h to form a P2 phase structure without impurities.
[0076] Method 3 The spray drying method comprises the following steps: A) dissolving a sodium source compound, a zinc source compound, an iron source compound and a manganese source compound in water according to a molar ratio, and mixing them by ball milling to obtain a precursor solution; B) injecting the precursor solution into a spray dryer for spray drying, and grinding after drying to obtain a precursor powder; C) The precursor powder is calcined twice in sequence to obtain the active material.
[0077] The sodium source compound can be selected from one or more of sodium oxide, sodium carbonate, sodium acetate, sodium nitrate, sodium oxalate and sodium citrate, preferably sodium oxide or sodium carbonate.
[0078] The zinc source compound can be selected from one or more of zinc acetate, zinc nitrate and zinc oxalate, preferably zinc acetate.
[0079] The iron source compound can be selected from one or more of ferric acetate, ferric nitrate and ferric oxalate, preferably ferric acetate.
[0080] The manganese source compound can be selected from one or more of manganese acetate, manganese nitrate and manganese oxalate, preferably manganese acetate.
[0081] The above methods disclose three exemplary preparation methods of the active materials of the present application. The following will disclose examples of their application based on the above active materials.
[0082] For example, the present application also provides a sodium ion battery positive electrode sheet, which is prepared from a positive electrode material (the aforementioned active material can be referred to as a positive electrode active material), a conductive additive, a binder and a solvent.
[0083] Among them, the conductive additive is selected from one or more of Super-P, carbon black, and Ketjen black; the binder is selected from one or more of polyvinylidene fluoride or polyacrylic acid, sodium carboxymethyl cellulose, and sodium alginate.
[0084] The solvent is selected from N-methylpyrrolidone or deionized water.
[0085] The present application also provides a method for preparing the above-mentioned positive electrode sheet of a sodium ion battery, which is prepared by mixing a positive electrode material, a conductive additive, a binder and a solvent, coating and drying. Alternatively, the materials are mixed, impregnated with a solvent and pressed into sheets.
[0086] The present application has no particular restrictions on the specific methods of mixing, coating and drying, and methods known to those skilled in the art may be used, such as scraping and drying.
[0087] The present application also provides a sodium ion battery; the battery is composed of a positive electrode, a separator, an organic electrolyte and a negative electrode metal sodium. The positive electrode is the positive electrode sheet of the sodium ion battery. The organic electrolyte is a carbonate electrolyte with a concentration of 0.1 to 2M (preferably 1M).
[0088] In the organic electrolyte, the solvent is selected from at least one of diethyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate and fluorinated ethylene carbonate. Preferably, the solvent is a mixed solvent of propylene carbonate and fluorinated ethylene carbonate; The solute is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, and sodium bis(trifluoromethanesulfonyl)imide, preferably sodium perchlorate.
[0089] The separator is preferably glass fiber.
[0090] Sodium-ion batteries have excellent performance and can therefore be used in large-scale energy storage devices such as solar power generation, wind power generation, smart grid peak regulation, distributed power stations or communication bases.
[0091] In order to further understand the present application, the high energy density, low cost sodium ion battery positive electrode material provided by the present application and its preparation method and application are described below in conjunction with the embodiments. The protection scope of the present application is not limited by the following embodiments.
[0092] Example 1 Step 1: Preparation of Na by sol-gel method 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2 cathode material The target product is Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2 compound, raw materials include sodium acetate, zinc acetate, ferric nitrate, manganese acetate, citric acid, and the solvent is deionized water.
[0093] Manufacturing method: The raw material metal ions and citric acid were dissolved in deionized water at a certain molar ratio of 1:2, placed in an 80°C oil bath, stirred and evaporated to form a gel. The gel was placed in an oven at 150°C and dried for 8 hours, and ground in a mortar to obtain a precursor powder.
[0094] The precursor powder was placed in a muffle furnace, heated at a rate of 2°C / min, and pre-calcined at 450°C for 6 hours in an air atmosphere to obtain an intermediate product. The intermediate product was placed in a muffle furnace, and calcined at 750°C for 15 hours in an air atmosphere at a rate of 2°C / min to obtain the target product. Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2.
[0095] Application Example 1-1 Preparation of Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2 cathode material electrode sheet The target product prepared above is mixed with Super P and binder polyvinylidene fluoride in a mass ratio of 7:2:1, and solvent N-methylpyrrolidone is added. After pulping, coating, drying and other steps, an electrode sheet containing the target product oxide positive electrode material is obtained.
[0096] Application Example 1-2 Assembled with the target product Na 0.67Zn 0.13 Fe 0.15 Mn 0.72 Sodium ion battery with O2 as the positive electrode.
[0097] The target product positive electrode sheet prepared above and the metallic sodium negative electrode were assembled into a sodium ion battery, GF / F was used as a battery separator, and the electrolyte was a carbonate electrolyte (1M NaClO4 PC solution containing 5 vol% FEC).
[0098] Figure 1 Figure A in the middle shows the XRD picture of the target product obtained in Example 1. It can be seen from the figure that the synthesized material has good crystallinity and the obtained target product belongs to the hexagonal crystal system P63 / mmc.
[0099] Figure 1 Figure B is a SEM image of the target product obtained in Example 1, from which it can be seen that the particle size of the obtained particles is 1-5 μm.
[0100] Figure 2 Figure A shows the target product obtained in Example 1 at 10 mA g -1 The charge and discharge curve under current density shows that the material has a high discharge capacity of 171.3 mAh g in sodium ion batteries. -1 And has a high output voltage of 4.6V.
[0101] Figure 2 Figure B shows the cyclic voltammetry curve of the target product obtained in Example 1 at a scan rate of 0.1 mV / s. It can be seen from the figure that the obtained cyclic voltammetry curve corresponds to the charge-discharge curve.
[0102] Figure 2 Figure C shows the target product obtained in Example 1 at 50 mA g -1 Energy density cycling stability under current density. As can be seen from the figure, the initial energy density is 413.98 Wh kg -1 .
[0103] Figure 2 Figure D shows the target product obtained in Example 1 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 57.9%.
[0104] Comparative Example 1 The preparation method is the same as that in Example 1, except that the raw material ratio is changed according to Na 0.67 Zn 0.28 Mn 0.72 O2 was added in a stoichiometric ratio.
[0105] Figure 3The XRD picture of the target product obtained in Comparative Example 1 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal crystal system P63 / mmc.
[0106] Figure 4 Figure A shows the target product obtained in Comparative Example 1 at 10 mA g -1 The charge and discharge curves under current density show that the material has a high discharge capacity of 134.14 mAh g when applied to sodium ion batteries. -1 .
[0107] Figure 4 Figure B shows the target product obtained in Comparative Example 1 at 10 mA g -1 The cycling stability under current density is shown in the figure. The capacity retention rate is about 31.8% after 50 cycles.
[0108] Example 2 The preparation method is the same as that in Example 1, except that the raw material ratio is changed according to Na 0.67 Zn 0.23 Fe 0.05 Mn 0.72 O2 was added in a stoichiometric ratio.
[0109] Figure 5 The XRD picture of the target product obtained in Example 2 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal system P63 / mmc.
[0110] Figure 6 Figure A shows the target product obtained in Example 2 at 10 mA g -1 The charge and discharge curves under current density show that the material has a high discharge capacity of 132.6 mAh g in sodium ion batteries. -1 .
[0111] Figure 6 Figure B shows the target product obtained in Example 2 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 50.2%.
[0112] Example 3 The preparation method is the same as that in Example 1, except that the raw material ratio is changed according to Na 0.67 Zn 0.18 Fe 0.1 Mn 0.72 O2 was added in a stoichiometric ratio.
[0113] Figure 7The XRD picture of the target product obtained in Example 3 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal crystal system P63 / mmc.
[0114] Figure 8 Figure A shows the target product obtained in Example 3 at 10 mA g -1 The charge and discharge curves under current density show that the material has a high discharge capacity of 167.51 mAh g in sodium ion batteries. -1 .
[0115] Figure 8 Figure B shows the target product obtained in Example 3 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 40.8%.
[0116] Example 4 The preparation method is the same as that in Example 1, except that the raw material ratio is changed according to Na 0.67 Zn 0.08 Fe 0.2 Mn 0.72 O2 was added in a stoichiometric ratio.
[0117] Fig. 9 The XRD picture of the target product obtained in Example 4 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal crystal system P63 / mmc.
[0118] Fig.10 Figure A shows the target product obtained in Example 4 at 10 mA g -1 The charge and discharge curves under current density show that the material has a high discharge capacity of 196.8 mAh g when used in sodium ion batteries. -1 .
[0119] Fig.10 Figure B shows the target product obtained in Example 4 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 37.8%.
[0120] Example 5 Step 1, solid phase method for preparing Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2 cathode material The target product is Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72O2 compound, the raw materials include sodium carbonate, zinc oxide, iron oxide, and manganese oxide. The raw materials are solid-phase ball-milled to obtain a precursor powder; the precursor powder is placed in a muffle furnace and calcined at 750°C for 15 hours at a heating rate of 2°C / min in an air atmosphere to obtain the target product Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2.
[0121] Application Example 5-1 Preparation of Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2 cathode material electrode sheet The target product prepared above is mixed with Super P and binder polyvinylidene fluoride in a mass ratio of 7:2:1, and solvent N-methylpyrrolidone is added. After pulping, coating, drying and other steps, an electrode sheet containing the target product oxide positive electrode material is obtained.
[0122] Application Example 5-2 Assembled with the target product Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 Sodium ion battery with O2 as the positive electrode.
[0123] The target product positive electrode sheet prepared above and the metallic sodium negative electrode were assembled into a sodium ion battery, GF / F was used as a battery separator, and the electrolyte was a carbonate electrolyte (1M NaClO4 PC solution containing 5 vol% FEC).
[0124] Fig.11 The XRD picture of the target product obtained in Example 5 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal crystal system P63 / mmc.
[0125] Fig.12 Figure A shows the target product obtained in Example 5 at 10 mA g -1 The charge and discharge curves under current density show that the material has a high discharge capacity of 168.01 mAh g in sodium ion batteries. -1 .
[0126] Fig.12 Figure B shows the target product obtained in Example 5 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 53.3%.
[0127] Example 6 Preparation of Na by spray drying0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2 cathode material The target product is Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2 compound, the raw materials include sodium acetate, zinc acetate, ferric nitrate, and manganese acetate. The raw material metal ions are dissolved in deionized water according to a certain molar ratio, and ball milling is performed to obtain a precursor solution. The precursor solution is injected into a spray dryer for spray drying, and then ground to obtain a precursor powder; the precursor powder is placed in a muffle furnace and calcined at 750°C for 15 hours in an air atmosphere at a heating rate of 2°C / min to obtain the target product Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2.
[0128] Application Example 6-1 Preparation of Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 O2 cathode material electrode sheet The target product prepared above is mixed with Super P and binder polyvinylidene fluoride in a mass ratio of 7:2:1, and solvent N-methylpyrrolidone is added. After pulping, coating, drying and other steps, an electrode sheet containing the target product oxide positive electrode material is obtained.
[0129] Application Example 6-2 Assembled with the target product Na 0.67 Zn 0.13 Fe 0.15 Mn 0.72 Sodium ion battery with O2 as the positive electrode.
[0130] The target product positive electrode sheet prepared above and the metallic sodium negative electrode were assembled into a sodium ion battery, GF / F was used as a battery separator, and the electrolyte was a carbonate electrolyte (1M NaClO4 PC solution containing 5 vol% FEC).
[0131] Fig.13 The XRD picture of the target product obtained in Example 6 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal crystal system P63 / mmc.
[0132] Fig.14 Figure A shows the target product obtained in Example 6 at 10 mA g -1The charge and discharge curves under current density show that the material has a high discharge capacity of 170.79 mAh g when used in sodium ion batteries. -1 .
[0133] Fig.14 Figure B shows the target product obtained in Example 6 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 57.9%.
[0134] Example 7 The preparation method is the same as that in Example 1, except that the raw material ratio is changed according to Na 0.67 Zn 0.16 Fe 0.13 Mn 0.5 O2 was added in a stoichiometric ratio.
[0135] Fig.15 The XRD picture of the target product obtained in Example 7 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal crystal system P63 / mmc.
[0136] Fig.16 Figure A shows the target product obtained in Example 7 at 10 mA g -1 The charge and discharge curve under current density shows that the discharge capacity of this material in sodium ion batteries is 121.2 mAh g -1 .
[0137] Fig.16 Figure B shows the target product obtained in Example 7 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 59.4%.
[0138] Example 8 The preparation method is the same as that in Example 1, except that the raw material ratio is changed according to Na 0.67 Zn 0.08 Fe 0.2 Mn 0..5 O2 was added in a stoichiometric ratio.
[0139] Fig.17 The XRD picture of the target product obtained in Example 8 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal crystal system P63 / mmc.
[0140] Fig.18 Figure A shows the target product obtained in Example 8 at 10 mA g -1The charge and discharge curve under current density shows that the discharge capacity of this material in sodium ion batteries is 143 mAh g -1 .
[0141] Fig.18 Figure B shows the target product obtained in Example 8 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 50.0%.
[0142] Example 9 The preparation method is the same as that in Example 1, except that the raw material ratio is changed according to Na 0.67 Zn 0.13 Fe 0.15 Mn 0..5 O2 was added in a stoichiometric ratio.
[0143] Fig.19 The XRD picture of the target product obtained in Example 9 is shown. It can be seen from the figure that the synthesized material has good crystallinity and the target product obtained belongs to the hexagonal crystal system P63 / mmc.
[0144] Fig. 20 Figure A shows the target product obtained in Example 9 at 10 mA g -1 The charge and discharge curve under current density shows that the discharge capacity of this material in sodium ion batteries is 133.9 mAh g -1 .
[0145] Fig. 20 Figure B shows the target product obtained in Example 9 at 10 mA g -1 The cycling stability under current density is shown in the figure. After 50 cycles, the capacity retention rate is about 67.1%.
[0146] The above describes in detail the structure, features and effects of the present application based on the embodiments shown in the drawings. The above are only preferred embodiments of the present application, but the present application does not limit the scope of implementation to what is shown in the drawings. Any changes made in accordance with the concept of the present application, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the description and drawings, should be within the protection scope of the present application.
Claims
1. An electrode active material for a sodium ion battery, characterized in that: The chemical formula of the active ingredient of the electrode active material is Na 0.67 Zn (0.28-x) Fe x Mn 0.72 O2,0 <x≤0.2。 2. A method for manufacturing an electrode active material for a sodium ion battery, characterized in that: The method comprises: Providing a precursor powder, comprising at least a sodium source compound, a zinc source compound, an iron source compound and a manganese source compound in a predetermined ratio; and The precursor powder is calcined, and the chemical formula of the active ingredient is Na 0.67 Zn (0.28-x) Fe x Mn 0.72 O2,0 <x≤0.2; Optionally, the precursor is obtained by a sol-gel method, a solid phase ball milling method, or a spray drying method.
3. The method according to claim 2, characterized in that The precursor is obtained by a sol-gel method, and the precursor further comprises an organic phase provided by a chelating agent; The calcination is carried out in an air atmosphere and is divided into a first calcination and a second calcination, and the first calcination is performed at a heating rate of 2-10°C / min, the temperature is raised to 350-600°C, and the temperature is kept until the organic matter is decomposed; the second calcination is performed at a heating rate of 2-10°C / min, the temperature is raised to 750-1000°C, and the temperature is kept for 10-24 hours until a P2 phase structure without impurities is formed; Optionally, the chelating agent comprises citric acid, oxalic acid, tartaric acid or ethylenediaminetetraacetic acid.
4. The method according to claim 2, characterized in that: The precursor is obtained by solid phase ball milling, the sodium source compound includes sodium oxide, the zinc source compound includes zinc oxide, the iron source compound includes iron oxide, and the manganese source compound includes manganese oxide; optionally, the precursor powder is calcined once, the heating rate of the calcination is 2-10°C / min, the temperature is raised to 750-1000°C, and the temperature is kept for 10-24h to form a P2 phase structure without impurities; Alternatively, the precursor is obtained by solid phase ball milling, and the calcination is divided into a first calcination and a second calcination, and respectively: the heating rate of the first calcination is 2~10℃ / min, the temperature is raised to 350~600℃, and the temperature is kept until the organic matter is decomposed; the heating rate of the second calcination is 2~10℃ / min, the temperature is raised to 750~1000℃, and the temperature is kept for 10~24h to form a P2 phase structure without impurities.
5. The method according to claim 2, characterized in that: The precursor is obtained by a spray drying method, and includes spray drying and grinding operations performed in sequence; the calcination is divided into a first calcination and a second calcination, and respectively: the first calcination has a heating rate of 2-10°C / min, the temperature is raised to 350-600°C, and the temperature is kept until the organic matter is decomposed; the second calcination has a heating rate of 2-10°C / min, the temperature is raised to 750-1000°C, and the temperature is kept for 10-24h to form a P2 phase structure without impurities.
6. The method according to claim 3 or 5, characterized in that: The sodium source compound includes one or more of sodium carbonate, sodium acetate, sodium nitrate, sodium oxalate and sodium citrate; The zinc source compound includes one or more of zinc oxide, zinc acetate, zinc nitrate and zinc oxalate; The iron source compound includes one or more of iron oxide, iron acetate, iron nitrate, and iron oxalate; The manganese source compound includes one or more of manganese oxide, manganese acetate, manganese nitrate and manganese oxalate.
7. A sodium ion battery positive electrode material, characterized in that: The electrode active material according to claim 1; Optionally, the positive electrode material is a slurry.
8. A positive electrode sheet, characterized in that: The positive electrode is prepared by pressing raw materials containing at least the positive electrode material according to claim 7, a conductive additive, a binder and a solvent.
9. A battery, characterized in that: include: The electrode active material according to claim 1, the positive electrode material according to claim 8, or the positive electrode sheet according to claim 8; Optionally, the battery is a secondary battery.
10. An electrical device, characterized in that: Comprising the battery as claimed in claim 9.
Citation Information
Patent Citations
Oxygen variable valence sodium ion battery positive electrode material containing transition metal vacancies and preparation method of oxygen variable valence sodium ion battery positive electrode material
CN114122383A
Sodium-ion battery precursor material and preparation method of sodium-ion battery positive electrode material
CN116081696A
Preparation and application method of fluorine-doped zinc-manganese-based layered oxide positive electrode material
CN117594782A
Positive electrode material for secondary cell containing silicate
JP2017045538A